Validation of the Instagram Usage, Behavior, and Emotional Reactions Questionnaire (IUBERQ) with an Indonesian Student Sample: A Rasch Model Approach - Tina Deviana; Nia Tresniasari; Bahrul Hayat; Irianto (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2025)
Instagram is one of the most popular social media platforms in the world, especially among teenagers and young adults, allowing users to share visual content and interact socially online (Ting, 2014). As the psychological and behavioral impacts of Instagram use increase, it is important to assess not only its frequency, but also the behavior and emotional responses that accompany it through valid and reliable measurement tools such as the Instagram Usage, Behavior, and Emotional Reactions Questionnaire (IUBERQ) (Paramboukis et al., 2016). This study aims to evaluate the psychometric characteristics of the Indonesian version of the Instagram Usage, Behavior, and Emotional Reactions Questionnaire (IUBERQ) instrument using the Rasch Rating Scale model approach. The population in this study were Muslim women who wear the hijab. The characteristics of the population used were female students of UIN Syarif Hidayatullah Jakarta aged 17-25 years. Respondents actively use Instagram social media accounts. The selection of this age is in accordance with the developmental stages from late adolescence to early adulthood to Hurlock (1999). The sample in this study amounted to 335 people. The results of the analysis using the Rasch Rating Scale Model show that the psychometric characteristics of the IUBERQ in the Indonesian version have a good level of precision and good item suitability to the model. These findings support the use of IUBERQ as a reliable instrument in measuring aspects of Instagram use. Theoretical and practical implications and recommendations for further research are also discussed